Multimedia projects in education : designing, producing, and assessing - Ivers, Karen S. 4 0 16; Barron, Ann E.; 5 (Westport, CT : Libraries Unlimited, 2006)
Shows teachers how to plan and assess student multimedia projects using the Decide, Design, Develop-Evaluate (DDD-E) model, and presents sample projects involving hypermedia, Web pages, presentation tools, and video, along with blackline masters and rubrics.
Impact of multimedia on student learning -- A model for the design and development of multimedia projects -- Decide -- Design -- Developing media elements -- Develop : multimedia development tools -- Evaluate -- Multimedia projects : hypermedia -- Multimedia projects : web pages -- Multimedia projects : presentation tools -- Multimedia projects : video.
Includes bibliographical references and index.
Professional;Professional
Keywords: 2 -- 0; 6; Design.;Design. -- Media programs (Education);Interactive multimedia.;Instructional systems;Media programs (Education);Multimedia.;Instructional systems; 20; 2